Mental Health Literacy in Zurich: A First Measurement Attempt Using the General HLS-EU-Q47 - Schneider, Michael; Jaks, Rebecca; Nowak-Flück, Daniela; Nicca, Dunja; De Gani, Saskia Maria (Frontiers in Public Health, 2021)
Background: Mental health literacy (MHL) promises to be an important factor for public health by enabling people to take responsibility for their own mental health. To date, there is no measurement tool that allows the assessment of a comprehensive understanding of MHL as part of health literacy (HL). Nonetheless, the widely used Health Literacy Survey European Questionnaire 47 (HLS-EU-Q47) includes items assessing at least some MHL-aspects in the context of HL. The present study aimed at investigating how these MHL-aspects are related to HL, health behavior and health outcome and how they differ between sociodemographic groups. Methods: Data from the Health Literacy Survey Zurich 2018, collected by an adapted version of the HLS-EU-Q47, served to investigate these relationships. Results: MHL-aspects were related to HL, health behavior and health outcome. Nearly half of all respondents (45 %; N = 904) showed low MHL levels, particularly those with higher age and higher financial deprivation. Conclusions: Relations of MHL-aspects with HL, health behavior and health outcome indicate their potential importance for future interventions in public health, addressing mental health and MHL. A specific MHL tool is needed to comprehensively investigate these relations, which could be developed by extending the present measurement approach.